Loran-C Latitude-Longitude Conversion at Sea : Programming Considerations - McCullough, James R.; Irwin, Barry J.; Bowles, Robert M. (The International Hydrographic Review, 2015)
To aid programmers of Loran-C latitude-longitude conversion, we : 1. Provide reference to the literature. 2. Compare digital “processings-noise” for several arc-length methods. 3. Discuss some practical aspects of overland signal propagation (ASF) modeling for offshore navigation. Comparisons are made of the precision of arc-length routines as computer precision is reduced. Overland propagation delays (ASF's) are discussed and illustrated with observations from offshore New England. Present practice of Loran-C error budget modeling is then reviewed with the suggestion that additional terms be considered in future modeling.